Using the Balanced Performance Approach to Increase the Effectiveness of Strategic Planning in order to Maximize the Job Satisfaction Rates at the Faculties of Bisha University - حبيب عادل محمد (Journal of Economics and Administrative Sciences, 2018)
Purpose: To use the balanced measurement approach as a strategic link for increasing the effectiveness of strategic planning in the direction of achieving satisfaction rates at Bisha University in Saudi Arabia Design / methodology / approach –The questionnaire survey was used to collect the data of the study from the faculty members at University of Bisha. Findings –Prove the assumption that the use of the balanced measurement approach - as a strategic planning tool - leads to maximize the satisfaction rates among faculty members at the University of Bisha. Research limitations/implications- adopt effective strategic planning in order to achieve job satisfaction rates in business organizations, especially education, by emphasizing the need to adopt a strategic link method to monitor strategic